A mahzor from Worms: art and religion in a medieval Jewish community - Ḳog'man-Apel, Ḳaṭrin (Harvard Univ. Press, 2012)
Introduction -- Facts about the Leipzig Mahzor -- Worms: community, society, and scholarship -- A Passover sermon by Eleazar ben Judah of Worms -- Halakhah and minhag: religious law and custom -- Musar: pietist ethics -- Sod: mystical dimensions -- Epilogue